Vitamin D – are we preventing the preventable?. (24th May 2012) - Jamieson, K; Thomas, J; Roueche, A; Hodes, D
Abstract : Aims: Following the introduction of the health start recommendations1 in 2006 a Camden based audit found only 19% of at risk children were being correctly supplemented. In an 18 month period (2009/10), we identified 6 patients from this ethnically diverse borough presenting to UCLH with hypocalcaemic seizures. This second cycle to close the audit loop will determine if this reflects a suboptimal change in community practice. Method: Having attained ethical approval, we are now delivering the same questionnaires to 100 consecutive parents attending community child health clinics in the UCLH area. Questions include age, ethnic background, breast or mixed feed, vitamin supplementation and who recommended them. We are assessing community health professionals' knowledge to see if they are aware of current guidelines and are giving correct advice to at risk groups. Data will be analysed and compared with the first audit cycle. Results: In the first cycle there was a parent questionnaire return rate of 80.6%. Average age of child ranged from 19 days to 5 years. 46 children were breast or mixed, 27 bottle fed and 2 did not specify. Only 9 received vitamin supplements, 5 following health visitor recommendations and 3 prescribed from hospital. 38 eligible children were not taking vitamin supplements, despite attendance at child health clinics. 2011 data will be compared to these figures along with professionals' knowledge. Conclusion: In view of a correct supplementation rate of only 19% from first cycle data it is clear that there is a failure to adequately identify at risk groups and follow department of health guidance. This clearly poses a clinical risk, as evidenced by patients presenting with complications, such as hypocalcaemic seizures. We will discuss the findings from our second cycle data in the context of the controversy and uncertainty that continues about the question of supplementation. We suggest that there is further focus on education to improved implementation of the NICE guidance2 .